Formation of Technological Cognitive Reason with Artificial Intelligence in Virtual Space - Evgeniy Bryndin (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Reason is the basis of our knowledge. It characterizes the mindfulness of thought activity, the ability to think universally, the ability to analyze, abstract, and generalize. Thanks to reason, computers, information technology, artificial intelligence, digital twins, cognitive robots have emerged. Using advances in science and technology, the international scientific and engineering community is trying to create an information technology mind. At the current stage of development of information technologies, cognitive robotics, digital twins and artificial intelligence systems, their synergy allows to begin to form a rational cognitive mind with artificial intelligence in virtual space. A cognitive virtual mind with artificial intelligence can be formed by a cognitive ensemble of intelligent mobile diversified agents with strong artificial intelligence through the regenerative development of professional skills, enhancing them visual, sound, subject, spatial, and temporal sensitivity.